GAMBARAN BERMAIN TERAPEUTIK SEBAGAI PENGALIHAN NYERI PADA PASIEN ANAK KANKER POST KEMOTERAPI DI RUMAH SINGGAH YAYASAN PEDULI KANKER ANAK BALI - Novita Lestari, Putu Santya; Utami, Kadek Cahya; Sri Krisnawati, Komang Menik (Coping: Community of Publishing in Nursing; Vol 8 No 3 (2020): Oktober 2020DO - 10.24843/coping.2020.v08.i03.p14, 2020)
Pain is one of the symptoms that is usually felt by cancer patients including children with cancer. Therapeutic play is one of intervention that is recommended for distraction in decreasing pain among post-chemotherapy cancer children. This aimed of the study was describing the mechanism of pain distraction by applying therapeutic play among post-chemotherapy cancer patients at Children's Cancer Care Shelter Foundation Bali. The population in this study was 36 children with cancer at Children's Cancer Care Shelter Foundation Bali. This study was conducting by applying quantitative research method and consisting of 11 samples in which those samples were selected by applying consecutive sampling . The data of this study was collected by observation form. The conclusion of this study shows that 76,6% and 60% of the respondents were under 11 years and were male respectively. Furthermore, 90% of all the respondents were suffered from leukemia 6,7% bone tumor, and 3,3% retinoblastoma. The pain level of the respondents before the therapeutic play were 0, 1, and 2. Meanwhile, types of therapeutic play that were played consisting of 46,7% coloring, 16,7% drawing, 23,3% playing puzzle and 13,3% of them played origami. The conclusion of this study shows that majority of respondents were under 11 years old, male, and has suffered from leukemia. Based on both pain assessment tools, it is known that most of children with cancer is in a mild pain category. Majority of respondents chose to play coloring-therapeutic play in 27 minutes. As suggestion, hopefully the future researcher can enlarge the sample size, describe the pain level after therapeutic play, and have a better time estimation for the research so it can be more optimized.